2006
DOI: 10.1007/s00246-005-1150-x
|View full text |Cite
|
Sign up to set email alerts
|

1173C>T Polymorphism in VKORC1 Modulates the Required Warfarin Dose

Abstract: The response to warfarin is highly variable among individuals and such variability is likely to have some genetic basis. We evaluted the effect of VKORC1 polymorphisms on warfarin response among Japanese, taking advantage of its unique population structure in which CYP2C9 *2 and *3 alleles are relatively rare. Thirty-one patients (12-34 years old; median, 22) on warfarin were recruited from a pediatric cardiology clinic. Genotyping of the C>T polymorphism at position 1173 in intron 1 of VKORC1 revealed that 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Interestingly, 2 small studies in Japanese patients also found a significant influence of VKORC1 on warfarin dose requirements. 25,33 In 31 Japanese patients older than 12 years (median age, 22 years; body weight Ͼ 40 kg), Kosaki et al found that VKORC1 heterozygotes required higher warfarin doses (in milligrams) than VKORC1 mutant homozygotes after adjustment for the INR value (P ϭ .003). 25 In 48 Japanese children (mean age, 6.6 years), Kato et al reported that age and the VKORC1 genotype were the main factors affecting the relationship between the weight-normalized warfarin dose and the INR value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, 2 small studies in Japanese patients also found a significant influence of VKORC1 on warfarin dose requirements. 25,33 In 31 Japanese patients older than 12 years (median age, 22 years; body weight Ͼ 40 kg), Kosaki et al found that VKORC1 heterozygotes required higher warfarin doses (in milligrams) than VKORC1 mutant homozygotes after adjustment for the INR value (P ϭ .003). 25 In 48 Japanese children (mean age, 6.6 years), Kato et al reported that age and the VKORC1 genotype were the main factors affecting the relationship between the weight-normalized warfarin dose and the INR value.…”
Section: Discussionmentioning
confidence: 99%
“…25,33 In 31 Japanese patients older than 12 years (median age, 22 years; body weight Ͼ 40 kg), Kosaki et al found that VKORC1 heterozygotes required higher warfarin doses (in milligrams) than VKORC1 mutant homozygotes after adjustment for the INR value (P ϭ .003). 25 In 48 Japanese children (mean age, 6.6 years), Kato et al reported that age and the VKORC1 genotype were the main factors affecting the relationship between the weight-normalized warfarin dose and the INR value. 33 Nevertheless, the influence of the CYP2C9 genotype could not be evaluated in these Japanese studies because of the very low allelic frequency of CYP2C9 variants in this ethnic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of retrospective [14][15][16][17][18][19][20][21][22][23] and prospective [11,[24][25][26][27][28][29][30][31][32][33][34] studies conducted since, have now clearly established the significant influence of polymorphism in CYP2C9 [9-11, 14, 15, 23, 24, 26, 28, 29, 32] and VKORC1 [9,10,23,26,28,32] genes on metabolism, and hence, the anticoagulant activity of warfarin. Thus, individuals homozygous for the CYP2C9*1 allele require a higher maintenance dose compared to the CYP2C9*2 (R 144 C) and CYP2C9*3 (I 359 L) homozygotes, respectively.…”
Section: Warfarin Metabolism and Pharmacogenomicsmentioning
confidence: 99%
“…13,15,17,[25][26][27][28]32,35,[44][45][46][47][49][50][51][54][55][56][57][58][59] The average warfarin dose for patients with the 1173 CC form is about 6 mg/day, the CT form is about 5 mg/day and the TT form of VKORC1 is approximately 3 mg/day. 35 In addition, differences in dose requirements among racial groups may be largely related to the prevalence of VKORC1 variants across populations 25,35,50 Another approach to evaluating the relationship between genotype and dose is to build a statistical model that incorporates a variety of factors (i.e., clinical, demographic and genetic) to estimate the influence of each factor on dose requirements, and also control for potential confounding factors.…”
Section: Observational Studiesmentioning
confidence: 99%